Professional Waqf in the Perspective of Maqāṣid al-Sharī‘ah: Concept, Implementation, and Challenges Analysis - Yunus, Hanafi (Jurnal Keislaman, 2026)
Professional waqf is an innovation in waqf practice that utilizes professional services, skills, and time as a form of sustainable contribution to the welfare of the community. This study aims to analyze the concept of professional waqf from the perspective of maqāṣid al-sharī‘ah, its implementation in Indonesia and other countries, the challenges it faces, and strategies for its strengthening and sustainability. This research employs a descriptive qualitative approach through library research, referring to classical literature, contemporary fatwas, and empirical practices. The findings reveal that professional waqf has a strong normative foundation and high relevance to the five main objectives of maqāṣid al-sharī‘ah, namely the protection of religion, life, intellect, lineage, and wealth. The implementation of professional waqf in various countries demonstrates diverse models, ranging from healthcare, education, legal aid, to economic empowerment. However, its development in Indonesia still faces regulatory constraints, low public awareness, limited support from professional associations, as well as technical and funding challenges. Therefore, strengthening strategies involving clear regulations, policy innovation, digital management, multi-stakeholder collaboration, and public education are crucial to positioning professional waqf as an adaptive, sustainable, and impactful Islamic philanthropic instrument.